Effect of COVID-19 on the cultural identity of the Amazonian indigenous Waorani - Aldrin Espín-León; María Luisa Pertegal-Felices; Antonio Jimeno-Morenilla; Juan Guzmán-Montalvo (Heliyon)
The indigenous peoples of the Amazon have experienced changes in cultural identity due to Western colonisation, contact with other cultures, migration, and pandemics. COVID-19, caused by the SARS-CoV-2 virus, affected all of humanity, including populations with limited contact with Western cultures, such as the Waorani indigenous people of the Amazon. Following the global pandemic, their culture may have undergone modifications. This study presents a comparative analysis of Waorani indigenous culture in the pre- and post-pandemic periods (2017–2022). In 2022, the same instrument designed to measure their culture in 2017 was applied, using the same methodology (participatory action in the territory) and in the same indigenous communities (88 individuals in 2017, 85 individuals in 2022). The results show that the cultural identity of the Waorani indigenous people has remained largely unchanged from the first measurement in 2017 to the second measurement after the pandemic in 2022 across most variables (economic, production, property, and land cultivation; family, reproduction, education, childcare, and medicine; organization, community politics, and justice; social, music, art, food, clothing, and housing). However, in the ideological, religious, beliefs, and spirituality domains, there was a significant decline in scores after COVID-19.